Global and bankrupt: Argentina’s fragmented integration into global capitalism - Elias, Friederike (Global economic elites and the new spirit of capitalism, 2024)
The amount of research on management in Argentina is rather limited. Though a broad range of studies deal with “economic elites”, many take a clearly economic point of view and deal with phenomena on the macro level.
Gesehen am 28.06.2024